Analisis Retorika dalam Pidato Perpisahan Presiden Joko Widodo: Harapan untuk Indonesia Emas 2045 - Karim, Nur Awalia; Subula, Rahmiyati; Maku, Nur Anisa; Djelema, Sartika; Dehiyo, Wardatul Magfirah; Pongoliu, Yulianti; Dama, Yunus (Jurusan Pendidikan Bahasa & Sastra Indonesia, Universitas Negeri Gorontalo, 2025)
At the end of his term, President Joko Widodo delivered his final State of the Nation Address at the Nusantara Building of the MPR/DPR/DPD, Jakarta on Friday, August 16, 2024. In this regard, this study will analyze the rhetoric of President Jokowi which contains hopes for a golden Indonesia 2045. This research is conducted with a qualitative approach and uses an analytical descriptive method, which identifies the rhetorical techniques applied in the speech entitled Hope for a Golden Indonesia 2045. The analysis was conducted to explore the message, structure, and language style used as well as to find out how the speech can influence the audience, as well as the meaning contained in the speech, in order to understand President Jokowi's efforts in conveying hope for Indonesia's future on YouTube live broadcasts. The results of this study show that the speech delivered by President Joko Widodo succeeded in persuading the audience by loading the three elements of rhetoric, namely ethos, logos, and phatos according to Aristotle. President Joko Widodo's speech titled “Hope for a Golden Indonesia 2045” uses effective rhetorical techniques, including an organized structure, simple word choice, and elements of ethos, logos, and pathos.